Efeito da terapia por fotobiomodulação sobre mecanismos de dor, em modelo experimental de tendinite induzida por colagenase - Capeloa, Cristina Nunes (2022)
Pain generated by tendinopathies is frequent and difficult to treat, but there are several therapies to alleviate this symptom, today, the most used is anti-inflammatory and when the pain is very intense and disabling, patients are treated with opioids. These drugs are used more frequently because they provide quick but momentary pain relief, presenting a risk due to their adverse effects, causing severe signs and symptoms, even irreversible effects on the individual's health. Therapy with Photobiomodulation appears to be a promising therapy for pain modulation, because until now, no adverse effects have been observed when compared to anti-inflammatories and opioids. The search for new therapies for the treatment of pain assumes a prominent role in the health area. The aim of this study was to evaluate and compare the effect of photobiomodulation therapy alone and associated with opioids on the pain process, in an experimental model of collagenase-induced tendinitis. Methodology: Male Wistar rats weighing between 300 and 400g, from the vivarium at UNINOVE Ethics Committee N 23222117019, were used. The animals were separated into groups: Control, with healthy tendon (CTL), Untreated tendinitis group (NT) Group treated with Photobiomodulation (808nm, 3J, 100 mW) (PBM), group treated with Tramadol Hydrochloride (Op), group treated with photobiomodulation + Tramadol hydrochloride (PBM+Op) and group treated with Naloxone and photobiomodulation (NL+PBM). For tendinitis induction, the animals in the groups were anesthetized and received a transcutaneous injection of Collagenase (100μg/animal) in the posterior region of the right and left paw, in the Achilles tendon. Eight hours after tendinitis induction, mechanical allodynia was assessed using the Radal Selito method and euthanasia was performed to remove the tendons for analysis, histology to check for inflammatory infiltrate and type I collagen; mechanical allodynia and MPO activity. Results: Treatment with PBM reduced MPO activity and maintained high collagen type I values. In mechanical allodynia, the group treated with PBM showed high pain resistance with values similar to the PBM + Op groups. The Op-treated group increased MPO activities and reduced type I collagen values. In mechanical allodynia, it showed a slight decrease in pain resistance when compared to the PBM and PBM + Op groups. The PBM + Op group showed similar values in mechanical allodynia to the PBM group, a decrease in MPO activity when compared to the Op group and a decrease in type I collagen. The NL + PBM group showed a decrease in pain resistance, becoming similar to the group NT and increased MPO activity. Type I collagen showed increased values when compared to the Op and PMB + Op groups. Conclusion: Our results showed that photobiomodulation had analgesic actions similar to opioids, in addition to decreasing MPO activity and preserving type I collagen in the tendon, suggesting a protective action.